ANALISA PENGARUH HEDONIC SHOPPING VALUE TERHADAP IMPULSE BUYING DENGAN SHOPPING LIFESTYLE DAN POSITIVE EMOTION SEBAGAI VARIABEL INTERVENING PADA MALL CIPUTRA WORLD SURABAYA - Lizamary Angelina Darma; Edwin Japarianto (Institute of Research and Community Outreach - Petra Christian University, 2014)
This study aims to analyze the influence of Hedonic Shopping Value on Impulse Buying at mall Ciputra World Surabaya by considering Shopping Lifestyle factor and Positive Emotion. This study uses 100 respondents and path analysis method. The research result obtained, there is no significant effect of Hedonic Shopping Value on Impulse Buying, there is a significant effect of Hedonic Shopping Value on Positive Emotion, there is a significant effect of Hedonic Shopping Value on Shopping Lifestyle, there is a significant influence of Positive Emotion on Impulse Buying, there is no significant influence of Shopping Lifestyle on Impulse Buying and there is a significant influence of Shopping Lifestyle on Positive Emotion